A review of optical errors and available applications of deflectometry technique in solar thermal power applications. (December 2019) - El Ydrissi, Massaab; Ghennioui, Hicham; Bennouna, El Ghali; Farid, Abdi
Abstract: The solar collectors represent a considerable part of the concentrated solar power plants, as their shape and quality determine the level of concentration focused on the receiver. Therefore, it is important to evaluate and characterize their quality based upon the influence of the optical errors. This analytical study illustrates the main optical errors that can occur during the manufacturing and the installation processes. In this scope, the Fringe Reflection Technique or Deflectometry, is a robust optical method that evaluates specular surfaces, and widely used and adapted in solar concentrators qualification process. The existing literature about this powerful technique emphasizes only its working principals, and none of them has ever provided a comprehensive detailed review about the different features of this technique. The main objective of this review is to summarize the different encountered optical errors which reduce the solar collectors' efficiency. The following review is also going to elaborate and classify the recent applications of the deflectometry on concentrated solar power technologies. Moreover, the contemporary methodologies and algorithms, constituting the core of this technique, are listed and compared according to their respective advantages and weaknesses. Finally, the recent developments and improvements of the deflectometry technique in other fields of study are mentioned according to their compatibility and practicality in the concentrated solar power field. Highlights: The main optical errors that can occur in a solar concentrator are reviewed. The different applications of the deflectometry technique used to qualify the solar reflectors are presented and classified. A comprehensive study of the methodologies and algorithms used in deflectometry theory is done and compared according to their advantages and weakness. The recent developments and improvements of the deflectometry technique in other fields of study are mentioned according to their compatibility and practicality in the CSP field.